A coupled 3D laser scanning and digital image correlation system for geometry acquisition and deformation monitoring of a railway tunnel. (September 2019) - Farahani, Behzad V.; Barros, Francisco; Sousa, Pedro J.; Cacciari, Pedro P.; Tavares, Paulo J.; Futai, Marcos M.; Moreira, Pedro
Highlights: A coupled 3D laser scanning and DIC system was innovated. 3D tunnel model tunnel profile was obtained by the system. Geometry acquisition and deformation monitoring of runnels were accomplished. 3D DIC was adopted to monitor the geometrical changes. Abstract: In this study, a 40 m-long section of a shallow railway rock tunnel so-called "Monte Seco tunnel" located at Vitoria Minas Railway in Brazil is investigated. In the real environment, the tunnel has been scanned by a 3D Terrestrial Laser Scanning (TLS) instrumentation and its geometry was reconstructed on a point cloud. Due to the complex geometry of the irregular rock face created by drill and blast, the obtained geometry lacked a number of regions (occlusions). In this study, a small-size model of the obtained point cloud was built through additive manufacturing and submitted to laboratory tests. A scaled demonstrator was developed for the acquisition of the 3D tunnel model profile with a Laser Scanning System (LSS), comprising a camera and a circular laser that scans the entire tunnel surface. After 3D geometry acquisition, the tunnel model was compressively loaded by imposing a displacement from the exterior wall and the deformation was monitored by a 3D Digital Image correlation (DIC) system setup adapted to the rail structure. Promising results have been accomplished and the achieved tunnel's point cloud verified the geometrical characteristics with minimum occlusions. Owing to obtained successful results on the geometry documentation, a real-scale 3D LSS model is presented for operation in a real environment.